Contextual Effect of School on Nutrition Intake to Prevent Anemia Among Female Adolescents in Yogyakarta - Ailsa Clarissa Cynara; Eti Poncorini Pamungkasari; Bhisma Murti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Inadequate nutritional intake can affect the body condition of young women, one of effects is increasing the incidence of anemia. The Health Belief Model theory can determine how a person will behave in deter